English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
3

Simplify:

3x + 11x = -2

2007-02-23 01:27:21 · 11 answers · asked by Anonymous in Science & Mathematics Mathematics

11 answers

3x+11x=-2

14x=-2

14x/14=-2/14

x=-2/14 or -1/7

2007-02-23 01:37:03 · answer #1 · answered by jAmPr0tzz 2 · 0 1

Do you mean "Solve" rather than "Simplify?"

Normally, we say "simplify" for an "expression" (as opposed to "solve" for an "equation"). An "expression" is a collection of terms and operations WITHOUT an equals sign. For example, you might be asked the following:

Simplify: 3x + 11x - 13 + 5

Answer: 14x - 8

Alternatively, an expression might be written with an equals sign followed by a question mark. Since you don't "multiply each side" of an equation that has a question mark on one side, this type of problem is the same as the "simplify" problem above. Notice that you CANNOT say the value of x in this type of problem, because you are not given a real equation:

Simplify: 3x + 11x - 13 + 5 = ?

Answer: 14x - 8

"Simplify" generally means "combine like terms to make the expression as compact as possible." We usually aren't asked to "simplify" an equation, as you asked. Usually we are asked to "solve" or "find the solution of" an equation.

The solution of an equation is the value of the variable that makes the equation true. "Solve for x" means "what must x equal for this equation to work?" We answer these problems by simplifying the left side, simplifying the right side, and then adding/subtracting/multiplying/dividing both sides by the same number in order to isolate the variable. For your equation:

Solve: 3x + 11x = -2

Answer:
14x = -2
14x/14 = -2/14
x = -1/7

Here's a more complicated one:

Solve: 3x + 11x - 13 + 5 = -2 + 2x + 8

Answer:
14x - 8 = 2x + 6
14x - 8 - 2x = 2x + 6 - 2x
12x - 8 = 6
12x - 8 + 8 = 6 + 8
12x = 14
12x/12 = 14/12
x = 7/6

2007-02-23 09:48:02 · answer #2 · answered by TK42 1 · 0 0

To simplify first you move the 2 over to the other side of the equation:

3x + 11x +2.

Then you can combine the like terms:
14x +2

you can leave it there or reduce that by 2 and get
2(7x+1)

2007-02-23 09:31:52 · answer #3 · answered by Remnant 2 · 1 0

3x + 11x = -2
14x = -2
x = -2/14 = -1/7

2007-02-23 09:30:51 · answer #4 · answered by Mathematica 7 · 1 0

3x + 11x = -2
14x = -2
x= -2/14
x = -1/7
x = -0.142857143

2007-02-23 09:41:12 · answer #5 · answered by buckeyebrowser 1 · 0 0

3x+11x= -2
14x = -2
x= -1/7

2007-02-23 09:31:20 · answer #6 · answered by jaybee 4 · 1 0

N = -2

2007-02-23 09:30:23 · answer #7 · answered by khorat k 6 · 0 3

3x+11x=-2
14x=-2
x=-2/14
x=-1/7

2007-02-23 11:30:53 · answer #8 · answered by Oni 2 · 0 0

Combine like terms:
14x=-2

Divide both sides by 14:
x=-2/14=-1/7

Check:
3(-1/7)+11(-1/7)=-2
-3/7-11/7=-2
-14/7=-2
-2=-2

I hope this helps!

2007-02-23 09:35:01 · answer #9 · answered by Anonymous · 0 0

3x + 11x = - 2

14x = - 2

14x/14 = - 2/14

x = - 2/14

x = - 1/7

- - - - - - - - - - - - - -s-

2007-02-23 10:23:02 · answer #10 · answered by SAMUEL D 7 · 0 0

fedest.com, questions and answers